GOOD OR BAD TEACHING PRACTICES? LEARNING FROM EFL CLASSROOMS - Tono Suwartono; Pipit Sri Mularsih; Khomsatun Khomsatun (Khazanah Pendidikan, 2022)
Many factors why EFL learners in Indonesia tend to think that English is difficult to learn, one of which is how the teachers "cook" the teaching learning process to make them "drooling" and "want to eat" English more and more. In other words, teachers should be able to make the "recipe", execute the recipe in sequence, and then "garnish the dish" to make the students tempted to enjoy the material taught. Hence, this article investigates the reasons why most EFL learners reluctantly learn English and and find it difficult to master it. Literature review method was conducted to explore this study which is hoped to answer the questions put forward within this study. No "wow" beginning and poor teacher creativities are some of the main issues of EFL teachers which result in reluctance in the part of students in learning process. Additionally, teacher talks time (TTT), teacher centered learning, and other factors are discussed in this paper to be overcome by EFL teachers. Therefore, training and workshops on creative teaching for teachers are encouraged to conduct and a better attention to EFL teachers' quality control from the schools management and stakeholers should be given.